The WRKY Transcription Factor Genes in Lotus japonicus - Hui Song; Pengfei Wang; Zhibiao Nan; Xingjun Wang (International Journal of Genomics)
WRKY transcription factor genes play critical roles in plant growth and development, as well as stress responses. WRKY genes have been examined in various higher plants, but they have not been characterized in Lotus japonicus. The recent release of the L. japonicus whole genome sequence provides an opportunity for a genome wide analysis of WRKY genes in this species. In this study, we identified 61 WRKY genes in the L. japonicus genome. Based on the WRKY protein structure, L. japonicus WRKY (LjWRKY) genes can be classified into three groups (I–III). Investigations of gene copy number and gene clusters indicate that only one gene duplication event occurred on chromosome 4 and no clustered genes were detected on chromosomes 3 or 6. Researchers previously believed that group II and III WRKY domains were derived from the C-terminal WRKY domain of group I. Our results suggest that some WRKY genes in group II originated from the N-terminal domain of group I WRKY genes. Additional evidence to support this hypothesis was obtained by Medicago truncatula WRKY (MtWRKY) protein motif analysis. We found that LjWRKY and MtWRKY group III genes are under purifying selection, suggesting that WRKY genes will become increasingly structured and functionally conserved.